The Development Model of Islamic Philosophy to Realize the Independence of Islamic Boarding Schools - Hadiyanto, Redi; Irwansyah, Shindu; Firdaus Nuzula, Zia (KnE Social Sciences, 2023)
The background of this research is to develop a model system of Islamic philanthropy management (zakat, waqf, infaq, alms). The location that is used as the object of research in applying the concept is the Darul Falah Islamic Boarding School in Cimenteng, Subang. The theory used in this research is the productive waqf theory which is an effort to renew the traditional waqf management to become more professional in increasing the benefits of waqf. This research aims to have economic development in order to carry out the wheels of life for pesantren programs, as a culture that must remain in the community. So that the ability of clerics, students, and the community becomes the main key in the life of the pesantren and continues to develop. The methods used in this study are descriptive and normative approaches from the data collected in the form of primary and secondary data. The results showed that the Islamic philanthropy management system at the Darul Falah Islamic Boarding School Cimenteng Subang, especially the management in the field of waqf with a productive waqf system developed by the Islamic boarding school with several assets managed in the form of workshops, mini markets, and agriculture, which were directly managed by professional Nazirs. They helped in providing significant results, which will later be used for the welfare of the Islamic boarding school community, and santri, kyai, ustad, and the entire community in the pesantren environment. Keywords: Waqf, productive Waqf, Islamic boarding school independence